2020
DOI: 10.1002/slct.202002755
|View full text |Cite
|
Sign up to set email alerts
|

A Phthalonitrile Resin with a Low Melting Point and High Storage Modulus Containing High‐Density Aromatic Ether Bonds

Abstract: A low melting point phthalonitrile monomer named 4,4'-((((((2cyano-1,3-phenylene)bis(oxy))bis(4,1-phenylene))bis(oxy))bis (4,1-phenylene))bis(oxy))diphthalonitrile (BOPN), was synthesized by nucleophilic substitution of 4,4'-oxydiphenol with 2,6dichlorobenzonitrile. The BOPN resin containing high-density aromatic ether bonds were prepared via bulk addition polymerization. Two kinds of polymers were prepared from BOPN monomer by using 4-(aminophenoxy)phthalonitrile (APPH) as the curing agent under different cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Although the oligomers in this study showed the lowest densities of cyano groups, the cured resins with relatively high T g s could be obtained through the relatively moderate curing conditions, 10,24,40,66,67 which was probably due to the secondary crosslinking of the methylene group. 68 In the secondary crosslinking reaction, some sp 3 carbon atoms of specific structures participate in the formation of isoindoline or self-coupling, allowing to generate a dense network and increase T g of resin.…”
Section: Thermal Properties Of Post-curing Resinsmentioning
confidence: 60%
See 2 more Smart Citations
“…Although the oligomers in this study showed the lowest densities of cyano groups, the cured resins with relatively high T g s could be obtained through the relatively moderate curing conditions, 10,24,40,66,67 which was probably due to the secondary crosslinking of the methylene group. 68 In the secondary crosslinking reaction, some sp 3 carbon atoms of specific structures participate in the formation of isoindoline or self-coupling, allowing to generate a dense network and increase T g of resin.…”
Section: Thermal Properties Of Post-curing Resinsmentioning
confidence: 60%
“…(PIPN-1-325 and PIPN-2-325 were prepared according to curing procedure a ; PIPN-1-350 and PIPN-2-350 were prepared according to curing procedure b ; PIPN-1-375 and PIPN-2-375 were prepared according to curing procedure c . ).
Figure 8.A comparison of this work to other oligomeric PN resins 10, 24, 40, 66, 67 in terms of cyano groups density, post-curing temperature, curing duration, and T g .
…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation